The unconstrained binary quadratic programming problem: a survey - Kochenberger, Gary; Hao, Jin-Kao; Glover, Fred; Lewis, Mark; Lü, Zhipeng; Wang, Haibo; Wang, Yang (Journal of combinatorial optimization, 2014)
In recent years the unconstrained binary quadratic program (UBQP) has grown in importance in the field of combinatorial optimization due to its application potential and its computational challenge. Research on UBQP has generated a wide range of solution techniques for this basic model that encompasses a rich collection of problem types. In this paper we survey the literature on this important model, providing an overview of the applications and solution methods.